Pleiotropic Effects of Secretin: A Potential Drug Candidate in the Treatment of Obesity? - Laurila, Sanna; Rebelos, Eleni; Honka, Miikka-Juhani; Nuutila, Pirjo (Frontiers in Endocrinology, 2021)
Secretin is the first hormone that has been discovered, inaugurating the era and the field of endocrinology. Despite the initial focus, the interest in its actions faded away over the decades. However, there is mounting evidence regarding the pleiotropic beneficial effects of secretin on whole-body homeostasis. In this review, we discuss the evidence from preclinical and clinical studies based on which secretin may have a role in the treatment of obesity.